Product Development of a Housing and Mounting System for a Vibration-Based Awning Sensor - Hemå, Petter; Johansen, Linnéa (My University, 2026)
This thesis presents the product development of a housing and mounting system for a vibration-based awning sensor intended to support automatic protection against windrelated damage. The project aimed to improve the reliability of automated awning systems by reducing the risk of weather-related damage, minimizing maintenance costs and enhancing user trust. Existing solutions, stakeholder needs and technical requirements were investigated to guide concept development, detail design, prototype testing and manufacturing adaptation. Following evaluation of different detection principles, the work focused on a vibration-based sensor mounted directly on the awning. The main focus was the physical housing and mounting solution, including protection of internal components, compatibility with different awnings, serviceability, outdoor durability, visual integration and manufacturability. The final concept consists of a compact sensor housing designed for injection molding, with a two-part construction sealed using a gasket. The concept uses a T-slot mounting solution for attachment to the awning and a bayonet mechanism enabling tool-free removal of the housing. 3D-printed prototypes were manufactured and evaluated regarding sealing performance, mounting compatibility and repeated handling. The results indicated good functionality and suitability for further development. The project concludes that the developed housing and mounting concept has potential to support reliable integration of vibration-based sensing in automated awning systems. Further work should include environmental testing, electronics integration and validation using productionready components.
Keywords: vibration sensor; awning systems; product development; housing design; mounting system